2009
DOI: 10.1590/s0102-311x2009000500009
|View full text |Cite
|
Sign up to set email alerts
|

Análise espacial da ocorrência de dengue e condições de vida na cidade de Nova Iguaçu, Estado do Rio de Janeiro, Brasil

Abstract: A reemergência da dengue, sua disseminação e manutenção vêm desafiando o sistema de saúde brasileiro. Fatores relacionados às condições de vida da população têm sido abordados na compreensão de diferentes desfechos em saúde. Este trabalho analisa a ocorrência da dengue e sua relação com as condições de vida no Município de Nova Iguaçu, Rio de Janeiro, Brasil, de 1996 a 2004. Os dados sobre ocorrência de dengue foram obtidos no Sistema de Informação de Agravos de Notificação (SINAN). Para caracterização das con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
(29 reference statements)
4
15
0
20
Order By: Relevance
“…Results similar to ours were found in the cities of Nova Iguaçu in the Baixada Fluminense, and in São José do Rio Preto, interior of São Paulo, where the highest incidence was observed in high or medium to high living status neighborhoods, contiguous to bad living status neighborhoods 19,20 .…”
Section: Discussionsupporting
confidence: 88%
“…Results similar to ours were found in the cities of Nova Iguaçu in the Baixada Fluminense, and in São José do Rio Preto, interior of São Paulo, where the highest incidence was observed in high or medium to high living status neighborhoods, contiguous to bad living status neighborhoods 19,20 .…”
Section: Discussionsupporting
confidence: 88%
“…Various studies have attempted to identify risk areas in cities and their social and environmental determinants 22,23,24,25,26,27,42 , producing controversial results, that is, some indicating poor neighborhoods as risk areas for dengue, and others the opposite, with wealthier areas as the riskiest 24,43 . This disparity of results may be the consequence of the spatial-temporal dynamics of dengue epidemics themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the distribution of dengue risk in urban areas in Brazil 22,23,24,25 including in the city of Rio de Janeiro 26,27 , focusing on its association with socioeconomic and environmental factors. However, there is little research on the underlying processes of diffusion in this spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have not found any particular patterns associated with unfavorable socioeconomic conditions (9,33,36), while the work by Barcellos,et al (37) in Porto Alegre associated dengue cases with favorable socioeconomic conditions. The relationship of these variables to dengue may be due to unclear socioeconomic segmentation in the city and the location of sectors with better conditions near those with poor conditions (38,39).…”
Section: Discussionmentioning
confidence: 94%
“…Consideration for socioeconomic variables is also important to improve surveillance systems because in each local scenario they influence the distribution of the disease (1,9).…”
mentioning
confidence: 99%